Regulation beyond growth. (February 2013) - Durand, Cédric; Légé, Philippe
De-growth theses point to a renewal of critical thinking able to link intellectual research projects and social movements. This paper provides an overview of some of the strands of arguments that are mobilised to criticise the 'growth obsession', and explains why issues raised by de-growth proponents are at odds with the regulationist research strategy. Both approaches are then critiqued for missing the connection between crisis tendencies and capitalist social property. However, the Gramscian–regulationist inheritance of paying accurate attention to institutional forms in shaping macroeconomic dynamics is still much needed in order to explore transition paths beyond growth.